Multicenter evaluation of preoperative and standalone embolization in meningiomas - Yu, Duan; Huang, Guohui; Shen, Jun; Li, Yanan; Xu, Jie; Xu, Ziwei; Li, Jian; Dai, Dongwei (Frontiers in Oncology, 2025)
BackgroundPreoperative embolization has been proposed to reduce intraoperative blood loss and facilitate meningioma resection, however its clinical utility remains debated. This multicenter study evaluated the safety, efficacy, and angiographic outcomes of preoperative embolization and standalone embolization in intracranial meningiomas.MethodsIn this retrospective cohort from January 2017 to January 2022, patients were stratified into three groups: standalone embolization (SE), combined preoperative embolization and craniotomy (hybrid surgery, HS), and craniotomy alone (control). Tumor characteristics, procedural metrics, and clinical outcomes were compared.ResultsCompared to control group, the HS group exhibited significantly larger tumors (68.8 ± 10.6 cm³ vs 35.7 ± 11.3 cm³, P<0.001) but achieved reduced intraoperative blood loss (9.8 ± 2.3 mL/cm³ vs 19.2 ± 6.5 mL/cm³, P<0.001) and higher gross total resection rates (70.1% vs 46.2%; P = 0.025). Compared to HS group, the SE cohort had smaller tumor volume (24.7 ± 5.2 cm³ vs 68.8 ± 10.6 cm³; P<0.001), better baseline neurological function score (median mRS 0 vs 1; P<0.001), and showed higher total devascularization rate (56.3% vs 25.4%; P = 0.008) after embolization procedure. Tumors in SE group were supplied exclusively by the external carotid artery (ECA). At a median 24-month follow-up, recurrence rates and neurological change were no different across groups.ConclusionHybrid surgery optimized surgical resection for large meningiomas by reducing blood loss and improving resection completeness, while standalone embolization demonstrated feasibility for select small tumors with ECA. Both two strategies showed acceptable safety and effectiveness.